Harmonious or Conflicted? A Qualitative Study of Father-Coach and Daughter Relationships in Youth Sport - Ormond, Isabel; Holt, Nicholas (Journal of Amateur Sport, 2022)
Representatives of some Canadian sport organizations have called for more research with parent-coaches in order to inform policy and educational initiatives. The purpose of this study was to examine perceptions of relationships between father-coaches and their daughters. Sixteen participants (eight father-coaches and eight daughters) completed individual interviews, which were transcribed verbatim and subjected to a dyadic analysis. Four dyads were coded as harmonious and four dyads were coded as conflicted. Certain factors differentiated between the harmonious and conflicted dyads. For example, in the harmonious dyads father-coaches adopted a relationship-oriented coaching approach and were consistent in their behaviors between home and sport settings. In the conflicted dyads, father-coaches adopted a more intense coaching approach and behaved differently in home versus sport settings. Father-coaches in the conflicted dyads were also much harsher on their own daughters compared to father-coaches in the harmonious dyads. These differentiating factors offer guidance that may inform training and educational opportunities specifically geared toward parent-coaches.